Neurodevelopment at 2 years corrected age among Vietnamese preterm infants. Issue 2 (12th July 2019) - Do, Chuong Huu Thieu; Kruse, Alexandra Yasmin; Wills, Bridget; Sabanathan, Saraswathy; Clapham, Hannah; Pedersen, Freddy Karup; Pham, Thanh Ngoc; Vu, Phuc Minh; Børresen, Malene Landbo
Abstract : Background: Preterm infants are at risk of neurodevelopmental delay, but data on long-term outcomes in low-income and middle-income countries remain scarce. Objectives: To examine neurodevelopment using Bayley Scales of Infant and Toddler Development-3rd edition (Bayley-III) and neurological findings in 2-year-old preterm infants, and to compare with healthy Vietnamese infants. Further, to assess factors associated with neurodevelopmental impairment. Design and setting: Cohort study to follow up preterm infants discharged from a neonatal intensive care unit (NICU) of a tertiary children's hospital in Vietnam. Participants: Infants born at <37 weeks of gestational age. Main outcomes: Bayley-III assessment and neurological examination at 2-year corrected age (CA) compared with healthy Vietnamese infants. Results: Of 294 NICU preterm infants, Bayley-III scores of all 184/243 (76%) survivors at 2 years CA were significantly lower than those of healthy Vietnamese peers in all three domains: cognition (mean (SD): 84.5 (8.6) vs 91.4 (7.5), p<0.001), language (mean (SD): 88.7 (12.5) vs 95.9 (11.9), p<0.001) and motor (mean (SD): 93.1 (9.0) vs 96.8 (9.3), p=0.003). The mean differences in Bayley-III scores between preterm and healthy Vietnamese infants were −6.9 (−9.1 to −4.7), −7.2 (−10.5 to −3.8) and −3.7 (−6.1 to −1.2) for cognitive, language and motor scores, respectively. The prevalence of neurodevelopmental impairment was 17% for cognitive, 8% for language and 4% for motor performance. In total, 7% were diagnosed with cerebral palsy. Higher maternal education was positively associated with infant neurodevelopment (OR 0.32, 95% CI 0.11 to 0.94). Conclusions: Vietnamese preterm infants in need of neonatal intensive care showed poor neurodevelopment at 2 years. Higher maternal education was positively associated with infant neurodevelopment. Standard follow-up programmes for preterm infants should be considered in low-resource settings.